Responsibility of the parties for breach of their obligations under the contract of carriage cargoes by motor transport - Волкова, Аліна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article refers to the protective function of the legislation on road transport. The author follows the positions of the escalation of accessory liability as a consequence of violation of their treaty obligations in civil liability under jurisdiction judicial protection of rights. Attention is paid to the shortcomings of current legislation including TVA is hopelessly out of date (Charter automobiles Ukrainian SSR) and its reduction to the needs of practice.